Současný stav vzdělávání učitelů anglického jazyka na Katedře anglistiky a amerikanistiky Fakulty humanitních studií Univerzity Pardubice - Kubrychtová, Irena (Univerzita Pardubice, 2003)
The case study forms a part of the British Council project Evaluation of Support for English Language Teaching in the Czech Republic. The main aim was to characterise the present state of pre-service ELTE at the Department of British and American Studies, Faculty of Humanities, University of Pardubice, and find out what influenced the process of its development. Two main issues were considered: the overall training process and teacher trainer's professional thinking. The area investigated within the overall training process issue was the curriculum, whereas within the overall teacher trainers' professional thinking, their perceptions of their own work, their professional development and thinking processes were investigated.
Keywords: vzdělávání učitelů; výuka angličtiny; studie